ANALISIS LOCATION QUOTIENT DAN SHIFT SHARE DALAM PENENTUAN SEKTOR UNGGULAN PEREKONOMIAN KABUPATEN PENYANGGA (Studi Kasus Di Kabupaten Sukoharjo Dan Karangnayar) - Ecclisia Sulistyowati; Tri Wisudawati; Wahyu Adhi Saputro (Magister Manajemen STIE Bank BPD Jateng, 2022)
Indicators of increasing economic development can be viewed through the numbers or values of economicgrowth. Indicators of the regional economy can also be seen from per capita income, economic growth and economic structure. Economic movements do not only occur in big cities but also occur in the supportingdistricts of the city, for example Karanganyar Regency and Sukoharjo Regency which are buffer districts from the existence of Surakarta City. The purpose of this study was to determine the leading sector of the economyof the buffer district. The data used in this study is secondary data in the form of time series sourced from the Central Statistics Agency for each area of Karangnayar and Sukoharjo Regencies. The data used are regionalgross domestic product (GRDP) data for each region from 2016 to 2020. The data analysis used in this studyis the analysis of location quotient (LQ) and shift share. Based on the results of the study, it is known that thereare basic sectors found in two buffer districts, namely Karanganyar Regency and Sukoharjo Regency. Theresults of the study based on LQ analysis stated that there were 7 base sectors in the Karanganyar Regency area while in the Sukoharjo Regency area there were 9 base sectors. If you look at the shift share analysis withindicators on the assessment of the component of regional share growth in Karanganyar Regency, there are 7 sectors that have positive values while in Sukoharjo Regency there are only 4 sectors that are still negative..